Characterization of Thermophilic Campylobacter SPP. in Commercial Broiler Chicken from Farm to Retail - Tang, John Yew Huat (2010)
The public health importance of thermophilic Campylobacter in man and limited data available in Malaysia led the present study to determine the prevalence of thermophilic Campylobacter from farm to retail and its potential of cross-contamination to cooked food. Campylobacter isolates were tested for their resistance and Multiple Antibiotic Resistance (MAR) index was determined. Currently, Campylobacter jejuni (physiology and metabolism) have not been fully understood. Thus, C. jejuni ATCC 33560 physiology and metabolism was being investigated using Phenotypic MicroArray (PM) technology to provide insight of C. jejuni carbon source utilisation and sensitivity towards osmolytes and pH. Prevalence of Campylobacter in chickens from farm to retail was determined using plating and Polymerase Chain Reaction (PCR) method. This study found no Campylobacter detected in cloacal swabs from chickens in farms practising close-house system but occurred at 95.0% in farms practising open-house systems. Prevalence of Campylobacter in chicken samples from conventional slaughterhouse and processing plant was 84.0% and 94.0%, respectively while Campylobacter contamination in chicken samples at wet market and supermarket was 78.0% and 92.0%, respectively. These showed chicken products are highly contaminated and it would be informative to know the Campylobacter load in chickens sold at retail level. Campylobacter load in chicken’s parts is determined using MPN-PCR method. Current investigation showed chicken meats and chicken by-products were contaminated with Campylobacter with their numbers ranged from <3 to 4600 MPN/g. In this study, chicken keels, chicken livers and gizzards harboured higher concentration of Campylobacter at 103-104 MPN/g compared to other chicken parts at 4.3%, 33.3% and 9.2%, respectively. Such high numbers of Campylobacter in chicken parts pose risk of human ingestion through contaminated food. Thus, C. jejuni cross-contamination from raw to cooked chickens was investigated. Campylobacter jejuni was found to contaminate cooked food regardless the food was left at room temperature (28±0.5oC) or taken directly from boiling water (100±0.5oC). Scored cutting boards were found to trap and transfer greater number of C. jejuni compared to untreated or new cutting boards. Scored cutting board made from rubberwood showed greater risk of cross-contamination than scored cutting board made from polyethylene. There was no significant different (P>0.05) between two types of cutting boards in untreated condition with regards to the number of C. jejuni transferred to cooked samples. Brief contact between raw chicken with cutting board was sufficient to contaminate the cutting board with C. jejuni. Hot samples rapidly lose heat (72-76oC) after taken from boiling water with the cutting process accelerated the heat loss. The findings suggested there are possibilities of Campylobacter being ingested by human through cooked chickens if proper hygienic practise is not practised in kitchen. Thus, it would be important to determine the antibiotic susceptibility profiles of Campylobacter isolates from chickens that might be ingested by consumers as this will determine the effectiveness of antibiotic regimen prescribed for infected individuals. Antibiotic susceptibility test was carried out on 126 Campylobacter isolated from retail commercial broiler chickens. Campylobacter showed high resistance to erythromycin (97.6%) and tetracycline (92.9%) while low resistance to gentamicin (35.7%) and nalidixic acid (35.7%). Campylobacter showed resistance towards all groups of antibiotics tested, namely beta-lactam (87.7%), cephalosporins (69.8%), quinolones (65.3%), chloramphenicols (84.9%), macrolides (97.6%), aminoglycosides (68.8%) and tetracyclines (92.9%). Of 126 Campylobacter spp. isolates, 0.8% showed resistant to five or less antibiotics, 60.3% showed antibiotic resistance to between six to ten antibiotics and 38.9% isolates showed resistance to more than 10 antibiotics. All isolates of Campylobacter spp. showed MAR index more than 0.20 which indicated there are abuse in antibiotic usage in chicken farming. In addition to antibiogram information, the present study also aimed to investigate the physiology and metabolism of Campylobacter that enable it to survive all the processes despite its fastidious characteristics and sensitivity to environmental stresses. The present study employed Phenotypic MicroArray (PM) technology to investigate C. jejuni metabolism and physiology. Phenotypic MicroArray (PM) profiles C. jejuni ATCC 33560 showed utilization of carbon sources from amino acids and carboxylates but not from sugars. Campylobacter jejuni ATCC 33560 is sensitive to NaCl at 2% and above but showed survival in a wide range of food preservatives (sodium lactate, sodium phosphate, sodium benzoate, ammonium sulphate and sodium nitrate). No phenotype loss was observed in carbon source plates when C. jejuni was incubated at suboptimal temperature. Phenotype loss of C. jejuni ATCC 33560 was observed in sodium chloride (1%), sodium sulphate (2-3%), sodium formate (1%), sodium lactate (7-12%), sodium phosphate pH 7 (100 mM and 200 mM), ammonium sulphate pH 8 (50 mM), sodium nitrate (60 mM, 80 mM and 100 mM), sodium nitrite (10 mM), and growth in pH 5. These results suggested that C. jejuni is still metabolically active at suboptimal growth temperature. This is the first study conducted in Malaysia to study the prevalence of Campylobacter in commercial broiler chickens from farm to retail, its cross contamination in food preparation as well as its physiology and metabolism. It can be concluded from this study that farm biosecurity is important to control Campylobacter. Despite the absence of Campylobacter in close-house farms, Campylobacter contamination in chickens at slaughterhouses and retails was still prevalent. Farmers, poultry processing plant operators and consumers should be aware of the importance of Campylobacter to human health and how to prevent its infection.